Доктрина Обами у зовнішній політиці США - Курандо, Олексій Сергійович; Курандо, Алексей Сергеевич; Kurando, Oleksii S. (My University, 2019)
Вибір теми був зумовлений необхідністю критично переглянути особливості так званої «доктрини Обами». Наукова проблема полягає у з’ясуванні ступню об’єктивності такої зовнішньої політики США, яку обрав президент Барак Обама, а отже й можливості її повторення у майбутньому. Вперше створено версію еволюції зовнішньої політики США з урахуванням відповідності доктрини Обами історично вкоріненим в США принципам «великої стратегії»; проведено аналіз пріоритетів зовнішньої політики США у 2008-2016 рр. відповідно до доктрини Обами й виявлено їх еволюцію протягом першої та другої адміністрації Б. Обами; визначено основні надбання й прорахунки адміністрації Обами та встановлено взаємозв’язок між ними; проаналізовано вплив суб’єктивного фактору на зовнішню політику США через вивчення постаті президента Обами. Як Дж. Буш – ст. та Б. Клінтон, Обама передав наступникові загальну програму та національну владу в кращому стані, ніж коли він прийшов до влади. Якщо виділяти найважливіші для США регіони, то це Великий Близький Схід, Південно-Східна Азія та Європа. Україна є важливою для США у контексті відносин із Росією. Більш реалістична американська стратегія щодо Росії має сполучати прямі переговори з істотним посиленням політики стримування з цілої низки питань. Це питання є принциповим для самих США, тому що центральним принципом організації американської зовнішньої політики залишається забезпечення глобального лідерства США.

Выбор темы обусловлен необходимостью критически пересмотреть особенности так называемой «доктрины Обамы». Научная проблема состоит в выяснении степени объективности той внешней политики США, которую избрал президент Барак Обама, а следовательно и возможности ее повторения в будущем. Впервые создана версия эволюции внешней политики США согласно исторически укорененным в США принципам «большой стратегии»; проведен анализ приоритетов внешней политики США в 2008-2016 гг. согласно доктрине Обамы и выявлена их эволюция в период первой и второй администрации Б. Обамы; определены основные достижения и просчеты администрации Обамы и установлена взаимосвязь между ними; проанализировано влияние субъективного фактора на внешнюю политику США через изучение фигуры президента Обамы. Как Дж. Буш – ст. и Б. Клинтон, Обама передал преемнику общую программу и национальную власть в лучшем состоянии, чем когда он пришел к власти. Если выделять самые важные для США регионы, то это Большой Ближний Восток, Юго-Восточная Азия и Европа. Украина важна для США в контексте отношений с Россией. Более реалистическая американская стратегия относительно России должна совмещать прямые переговоры с существенным усилением политики сдерживания. Это принципиально для самих США, так как центральным принципом организации американской внешней политики остается обеспечение глобального лидерства США.

The thesis provides a thorough study of the evolution of US policy under the influence of the adoption of the Obama Doctrine. The urgency of this topic is determined by an indisputable fact that at the beginning of the 21 st century there is an urgent need to critically review the peculiarities of the so-called “Obama Doctrine”, and to ascertain the degree of objectivity of such a policy, and hence a possibility to repeat its implementation in the future. The study of this issue is of great scientific importance, since only a few aspects of Obama's foreign policy have been investigated. The urgency of the topic is also explained by the important place that the US takes in Ukraine's politics. The scientific novelty of the results is as follows. For the first time, the conceptual foundation of Barack Obama’s policy has been analyzed and, accordingly, an authored version of US foreign policy evolution has been created, taking into account the correspondence of Obama Doctrine to historically rooted in the United States principles of Big Strategy; an analysis of US foreign policy priorities in 2008- 2016 was conducted and their evolution within the first and second presidential terms of Obama was revealed; main achievements and miscalculations of the Obama administration were identified and the connection between them was found; the influence of a subjective factor on US foreign policy through the study of President Obama’s figure is analyzed. Definition of the most important regional policies of the US and the politically determined role of the United States in each of the regions acquired further development as well as a holistic understanding of the peculiarities of contemporary US foreign policy in the context of changes in their internal policy and in the system of international relations; forecasting of the US foreign policy strategy in the medium-term perspective. The concept of “reasonable force”, “concept”, “strategy”, “Big Strategy”, and “doctrine” on the basis of the research of modern Ukrainian and foreign scientists’ works is specified; the importance of political values as one of the indicators of US influence on the modern system of international relations. Some conclusions drawn by the author of the study may be taken into account in the process of resolving the conflicts that Ukraine is currently engaged in. By Obama’s example, one can study an important procedure for coordinating a US foreign policy strategy construction at all stages: from a scientific concept through the adoption of official doctrine to its implementation into everyday practice. There are objective criteria which can help to assess the foreign policy of the presidential administration – the ability to fulfil what was promised, the weakening of the country’s enemies and strengthening of friends, the development of foreign policy doctrine in accordance with American interests. As George H. W. Bush and Bill Clinton, Obama gave the successor a general program and national power in a better condition than when he only came to power. The key to Obama’s success was his understanding of the overall picture: his belief in the liberal international order that the United States has cultivated over the past seven decades, along with recognition that the basis of this order should be saved by extracting from mistakes and hostility on the world's periphery. Obama’s own practice has shown that the international system has much less moral unity and security than an individual state. Therefore, challenges to world politics are not similar to the challenges of civil organization at the local level. The objectives of the US president are to promote the national interests of the United States abroad, guided by a sense of prudence and justice. If we select the most important regions for the US, we can assume that it is the Greater Middle East, Southeast Asia, and Europe. As for Ukraine, it is important for the USA only in the context of relations with Russia. The United States’ role in terms of finding a way out of the current stalemate in the Russian-Ukrainian conflict can be much more active. The United States must impose wider economic sanctions on key sectors of the Russian economy; provide new military assistance to the Government of Ukraine; conduct joint training, intelligence teams and observation; support economic reforms and political stability inside Ukraine by increasing financial and technical assistance. The United States must implement hybrid pressure strategies on Moscow, support US allies and protect the interests of the USA. A more realistic American strategy for Putin's Russia should combine direct negotiations in limited areas with a substantial strengthening of containment policy on a range of issues. This question is fundamental for the United States itself, as the central principle of the American foreign policy organization remains the provision of global US leadership. From this perspective, an important task for the US is to promote their model of development, ideals and values that the United States considers universal.
Курандо О. С. Доктрина Обами у зовнішній політиці США : автореф. дис. ... канд. політ. наук : 23.00.02 / О. С. Курандо ; Нац. ун-т "Одеська юридична академія". - Одеса, 2019. - 17 с.
Keywords: доктрина Обами; зовнішня політика; США; велика стратегія; «розумна сила»; доктрина Обамы; внешняя политика; США; большая стратегия; «умная сила»; Obama Doctrine; foreign policy; the USA; Big Strategy; smart power